Building Pancasila Values in Early Childhood Education at Klasis Flores - Maryance Ferawati Tamelab; Efraim Semuel Nalle; Irony Damianus Saefatu; Petrus Logo Radja; Retno J. K. Lopo; Agnesti Pae (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to evaluate early childhood character development in Klasis Flores by implementing the Pancasila Student Profile, particularly in the post-pandemic period, which prompted a shift to technology-based learning. Using a descriptive quantitative method, we collected the data through surveys, observation, interviews, and documentation. The outcomes show that kids are independent, believing, and ethical yet, at the same time, inadequate in imagination, worldwide mindfulness, tolerance, and innovation. Unsurprisingly, progress was uneven, demonstrating the need for further guidance from teachers. These findings underscore the essential character-building approach to address challenges in distance learning in rural areas.Â